Introduction: Connecting Translation and Network Studies - Folaron, Deborah; Buzelin, Hélène (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe expanding field of network studies, which comprises histories, traditions and innovative research from myriad disciplines such as mathematics, the social sciences, linguistics, computer science, physics, biology, Internet and communication studies may find meaningful dialogue with the field of translation studies. This introductory article seeks to present a multifaceted and multi-tiered historical trajectory of the term and concept “network”, reflecting on the impact it has already had on studies in the domain of the sociology of translation. Can a network-based vocabulary emerging from network theories and studies, including recent works on network society, offer translation studies new conceptual tools with which to think through and articulate translation phenomena? By the same token, how might translation studies, viewing interlingual transfer in terms of product, process, profession, industry, politics and strategy, contribute to the growing body of research on the transmission and exchange of thoughts, ideas, messages, information, values, which characterize communication, the core of all translation activity? As connectivity and connectedness take on ever-important social organizing dimensions in a globalizing multilingual world, a translation-informed network approach as well as a network-informed translation theory approach may symbiotically help us better understanding human and social practices.